2016
DOI: 10.1210/jc.2015-3694
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cortisone Reflects Cortisol Exposure Under Physiological Conditions and After Hydrocortisone

Abstract: In this study we tested the use of salivary cortisol and cortisone as alternatives to serum cortisol. Salivary cortisol is often undetectable and contaminated by hydrocortisone. Salivary cortisone strongly reflects serum cortisol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(119 citation statements)
references
References 30 publications
9
106
2
2
Order By: Relevance
“…To overcome the problem of lower performance characteristics due to low levels of salivary cortisol, instead of going for immunoassays, a better solution may be to measure salivary cortisone that is present in a much higher concentration than salivary cortisol. At a serum cortisol below 74 nmol/L, Debono et al 28 showed that salivary cortisol could become undetectable by LC-MS/MS, while salivary cortisone was always detected. Similarly, our data showed that after dexamethasone suppression, when the salivary cortisol became too low to be measured with LC-MS/MS in many subjects, salivary cortisone could still be measured in all but one subject in the eucortisolism group.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the problem of lower performance characteristics due to low levels of salivary cortisol, instead of going for immunoassays, a better solution may be to measure salivary cortisone that is present in a much higher concentration than salivary cortisol. At a serum cortisol below 74 nmol/L, Debono et al 28 showed that salivary cortisol could become undetectable by LC-MS/MS, while salivary cortisone was always detected. Similarly, our data showed that after dexamethasone suppression, when the salivary cortisol became too low to be measured with LC-MS/MS in many subjects, salivary cortisone could still be measured in all but one subject in the eucortisolism group.…”
Section: Discussionmentioning
confidence: 99%
“…It is noninvasive, painless, has no requirement for clinic attendance and reflects serum‐free cortisol, and there is less risk of false‐positive results, generated by the cortisol stress response to venipuncture, when testing for Cushing's disease. Recent evidence suggests that salivary cortisone is a better reflection of serum total and free cortisol than salivary cortisol . Serum‐free cortisol and salivary cortisol are rapidly oxidized to inactive cortisone, by 11β‐hydroxysteroid dehydrogenase type 2 (11β‐HSD‐2), which is responsible for the large difference in the proportion of salivary cortisol:cortisone (1:6) compared with that in serum (4:1) .…”
Section: Introductionmentioning
confidence: 99%
“…The results pointed to the decreased 11β-HSD2 activity and a dysfunction in the 5α-reductase pathway in depressed patients. This method allowed the assessment of 11β-HSD1/2 and 5α/β-reductase activities in a single analytical run providing an innovative tool to explain the potential etiology of depression [13].…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…The quantity of antigen is inversely proportional to the radioactivity estimated in test tubes. By plotting binding values against a succession of calibrators with known amounts of cortisol, a calibration curve is created, from which the anonymous concentration of cortisol in individual samples is determined [13].…”
Section: Cortisol Measurement and Reagent Preparationmentioning
confidence: 99%
See 1 more Smart Citation